Remediasi Miskonsepsi Mahasiswa Menggunakan Model Concept Attainment Pada Materi Metabolisme Sel - Afandi, Afandi (978-602-7561-892)
The purpose of this research is to investigate the effect of remediation misconception using concept attainment model. The method of this research is pre-experimental using one group pretest and posttest design. The sample is 1st semester pre-service teacher student at Biology Education Department, Tanjungpura University consist of 30 students. The instrument used is multiple choice diagnostic test. Statistic test used is paired sample t-test. The result shows remediation using concept attainment model gives significant effect with ES value 1.44.